Pengaruh Lokasi, Bagi Hasil dan Promosi terhadap Proses Keputusan Nasabah Menabung di PT Panin Dubai Syariah Bank - Erik Rif’ad Hendra Putra; Ade Sofyan Mulazid (Institut Agama Islam Negeri Kendari, 2018)
The purpose of this resesarch was to analyze the effect of location, reveneu sharing and promotion simultaneously and partially to decision process to save in product tabungan Flexible in PT Panin Dubai Syariah Bank Jakarta. The sample used in this study were 74 respondents from the customers of PT Panin Dubai Syariah Bank. The analytical method used is multiple linear regression analysis. The data obtained is the primary data that is the result of the respondents' answers to the questionnaire were distributed. These results of this study indicate that there is influence imultaneously on location variable, revenue sharing and promotion towards decision process to save. In the test of determination, there is the influence of a variable 51,9% location, revenue sharing and promotion to the decision to save. Meanwhile 48,1 %% (100% - 51,9%) were influenced by other variables that not included in this study. The result of this research showed that the location effect partially to the decision process to save, with significant value that is 0,021 < 0,05 and t count <t table (2,364 >1,993). Revenue sharing do not effect partially to the decision process to save, with a significant value of 0,503 > 0,05 and t count < t table (0,674 < 1,993). Promotion effect partially to the decision process save, with significant value that is 0,000 <0,05 and t count > t table (4,193 > 1,993)